Assessment of basic knowledge on colorectal cancer and its prophylaxis in people living in small city and countryside - Anna Roszkowska; Justyna Kwolczak; Łukasz Świerszcz; Halina Piecewicz-Szczęsna (Journal of Education, Health and Sport, 2018)
Introduction: Colorectal cancer is the third most common cancer in the world in men (660,000 cases, 10%) and the second in women (570,000 cases, 9%). Almost 60% of cases occur in developed countries. Colorectal cancer is second most common type of cancer in European countries, after lung cancer in men and breast cancer in women. Mortality from colorectal cancer in Poland is higher among men than the average for European Union countries - in 2010, the mortality rate was about 50% higher than the average for European Union countries. Materials and methods: Voluntary and anonymous research was conducted in 2017 and 2018 among 300 adult people, who were randomly selected. The study used the method of a diagnostic survey, while the research tool consisted of original questionnaire. The questionnaire contained 16 questions. The collected material was subjected to descriptive analysis. Values of the analyzed parameters were measured on a nominal scale and characterized by means of numbers and percentages. The data elaboration was based on a Microsoft Excel spreadsheet. Results: In reference to the collected data, vast majority agreed genetical factor to be crucial in developing of colorectal cancer, as 83% of subjects choose this answer in a multiple-choice question. Another multiple-choice question revealed that almost all questioned people associated rectal bleeding with symptoms of colorectal cancer – 94%. 29% of respondent admitted having a colonoscopy. Furthermore, over a half of respondents is aware of existing prophylactic programs in Poland. Conclusions: In reference to the survey, little of respondents perceive alcohol and red meat as risk factor for colorectal cancer development. Respondents who admitted having colonoscopy account for way too little group of people, from a perspective of analyzed age group. Still, little of them admitted seeing a doctor after suspicious signs/symptoms occurred.